2006
DOI: 10.1213/01.ane.0000237267.75543.59
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Neuraxial Block Versus General Anesthesia for Elective Total Hip Replacement: A Meta-Analysis

Abstract: Patients undergoing elective THR under neuraxial anesthesia seem to have better outcomes than those under GA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
127
1
12

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(148 citation statements)
references
References 16 publications
8
127
1
12
Order By: Relevance
“…Neuraxial anesthesia improves perioperative outcome and reduces mortality compared with general anesthesia in patients who have had a TJA [12,15,16,20,21]. However, we are aware of only one study comparing neuraxial Values are mean ± SD or mean with percentage in parentheses; ASA = American Society of Anesthesiologists.…”
Section: Discussionmentioning
confidence: 99%
“…Neuraxial anesthesia improves perioperative outcome and reduces mortality compared with general anesthesia in patients who have had a TJA [12,15,16,20,21]. However, we are aware of only one study comparing neuraxial Values are mean ± SD or mean with percentage in parentheses; ASA = American Society of Anesthesiologists.…”
Section: Discussionmentioning
confidence: 99%
“…Brown et al also found that the hypnotic depth might be associated with the one-year mortality rate in elderly patients during repair of hip fractures under spinal anesthesia. 23 We suggest that the long-term benefit of NA may be related to the more stable hemodynamic profile 24 and the shallower hypnosis associated with NA than in those seen with GA. Another possible reason is that orthopedic surgery under NA is associated with less blood loss and blood transfusion requirement than are found with GA. 4,5,25,26 Blood transfusion were identified as a predictor of long-term mortality following primary TJR in elderly individuals in a previous study. 27 Although not statistically significant at the 0.05 level, it is apparent that there was a slightly lower co-morbidity index amongst patients in the NA group after propensity-score matching.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Previous studies reported that orthopedic procedures under NA may be associated with a lower 30-day overall complication rate, better 30-day survival, a shorter hospital stay, and fewer blood transfusions than general anesthesia (GA). [4][5][6][7][8] Considering the short-term benefit, NA may be preferable for patients undergoing TJR. Little is known about the effect of anesthetic management on longterm outcomes.…”
Section: Résumémentioning
confidence: 99%
“…6 Second, the appropriate administration (dose and timing) of perioperative anticoagulant prophylaxis is important to mitigate the risk for both VTE and wound-site bleeding and to facilitate the administration of surgical anesthesia and postoperative analgesia, which by themselves can facilitate patient recovery. 7 Against this background, the objectives of this article are (a) to review, through case-based scenarios, the evidence surrounding VTE prophylaxis; (b) to discuss a recently recommended and validated stratification model for postoperative VTE; and (c) to provide state-of-the-art guidance for perioperative prophylaxis. We address special populations, including cancer surgery, bariatric patients, those with a history of heparin-induced thrombocytopenia (HIT) or heparin allergy, and neuraxial anesthesia.…”
Section: Résumémentioning
confidence: 99%